A Country on the Move : Domestic Migration in Two Regions of Myanmar - World Bank Group (World Bank, Yangon, 2016)
In the last four years Myanmar’s economy has seen a slight shift away from agriculture toward industry and services. This may mark the beginning of a structural transformation away from a rural, agricultural economy toward a more urban, industrial and service-based economy. Urbanization and job creation in urban areas have the potential to have a significant impact on labor and mobility patterns, especially for the landless and land-poor workers that account for a large part of the rural workforce. Domestic migration has been a critical component of the way many other countries in the region, including South Korea, China, and Vietnam, have managed to reduce poverty and support resilient livelihoods. However, pursuing these opportunities often entails significant risk for poor migrant households, who often have little capacity to absorb the shocks of failed migration attempts. Developing access to a knowledge base that enables them to manage risk more easily and make more informed choices around migration is critical to supporting their livelihoods. Migration flows can also have long-term social and economic consequences in rural areas as members of the labor force, particularly young people, move into cities and towns. This entails major public policy choices around areas such as spatial development, urbanization, service delivery, and poverty reduction. The government will need information on anticipated migrant flows in order to make the right policy choices and to plan for and provide services to people arriving from rural areas into urban settings. Within this evolving context, understanding the motivations, patterns, and dynamics of existing migration practices is critical in order to assist balanced and inclusive development in Myanmar by supporting safe and informed migration. The primary objective of this study is to collect detailed evidence and provide an objective assessment of how, and to what extent, migration within and from particular regions of Myanmar affects the livelihoods of rural households and the social and economic environment of villages. It seeks to understand how migration decisions take place, the key obstacles and risks faced by migrants, and the individual and household strategies that evolve to manage them. It also seeks to capture broader changes over time in sending communities, and how the departure and return of migrants affects social and economic dynamics at home and within the village. The study focuses on the Ayeyarwady Region and the Magway Region of Myanmar, which are home to large numbers of Myanmar’s rural poor and are also close to two of the major centers of growth and job creation in the country, Yangon and Mandalay respectively. In these areas, the study applies a mixed-methods approach to the four key questions outlined.